Effect of enzymatic treatment on rheological properties, glass temperature transition and microstructure of date syrup. Issue 1 (January 2015) - Abbès, Fatma; Masmoudi, Manel; Kchaou, Wissal; Danthine, Sabine; Blecker, Christophe; Attia, Hamadi; Besbes, Souhail
Abstract A knowledge of rheological properties is of importance in processing, handling, process design, product development and quality control. This study investigates the effect of commercial hydrolytic enzymes (pectinase and cellulase) on rheological properties and glass temperature transition of date syrup. Date syrups obtained by enzymatic extraction exhibited a quasi Newtonian behaviour. The enzyme-treated date syrups showed the highest values of activation energy (Ea). Therefore, these syrups showed the most temperature dependency. Dynamic shear results revealed viscous behaviour for date syrups indicating that both syrups displayed liquid-like behaviour. Temperature significantly affected both (G′) and (G″). The glass transition temperature (Tg) of date syrups varied between −39.56 and −45.74 °C depending on their composition. Glass transition temperature of date syrups decreased linearly with an increase in water content.